A comparative analysis between a newly Malaysian size ATD and the current Hybrid III ATD in frontal impact. Issue 1 (31st December 2022) - Abdul Samad, M. S.; Mohd Nor, M. K.
Abstract: The Hybrid III 50 th percentile (H350) Anthropomorphic Test Devices (ATD) is the most widely used crash test dummy to identify the best seatbelt and airbags configuration for frontal impact load cases. However, the H350 was developed based on the United States (US) anthropometric size, back in 1976. In other words, the restraint system optimized using the H350 is not optimized for other populations. To investigate this issue, a finite element model of Hybrid III 50 th percentile (H350M) of Malaysian population was developed and analysed in this work. Validation of the new biofidelity corridors was performed to ensure that this newly crash test dummy can represent the population under consideration. In this study, the H350M was integrated into a finite element vehicle model, to simulate a frontal rigid barrier crash load case performed at 56 km/h and compared with the existing H350. The H350 integrated vehicle-occupant simulation model has been correlated with a physical test. The model managed to achieve the average Correlation and Analysis (CORA) rating of 0.722. The simulation results showed that the newly H350M experienced a higher head acceleration, Head Injury Criterion (HIC15), 3 ms chest acceleration and chest displacement compared to the H350, as they were increased from 64.3 g to 70.6 g, 370 to 542, 49.6 g to 52.6 g, and from 26.5 mm to 26.6 mm, respectively. Generally, higher head acceleration, HIC15 and chest displacement lead to higher injuries during frontal crash accidents. Hence, the recommendations to reduce injuries are also discussed and explored in this study.